THE EFFECT OF DOW JONES INDEX AND INDONESIA MACRO VARIABLES INDEX ON FINANCIAL SECTOR PRICE INDEX POST GLOBAL FINANCIAL CRISIS 2008 - Aris Andika, Yusup; Said Djamaluddin (Dinasti Publisher, 2020)
This study aims to determine whether the Dow Jones Index, exchange rate, interest rates, and inflation affect the Financial Sector Stock Price Index. The population in this study is the Financial Sector Stock Price Index (CSPI) data from December 1995 to December 2018. The sample in this study is the monthly data of the Dow Jones Index, Rupiah Exchange Rates, SBI Interest Rates, Inflation, and CSPI within 10 years (120 months) from January 2009 to December 2018 where the CSPI experienced fluctuations during this period. The data analysis technique used is multiple linear regression. Research results show that Simultaneously, the Dow Jones Index variables, Dollar Exchange Rate, BI Rate, and Inflation significantly influence the dependent variable of the JCI movement with a coefficient value of 96.53%. The Dow Jones Index variable partially has a significant effect and is positively correlated with the CSPI dependent variable. Dollar Exchange Variable partially has a significant effect and negatively correlates to the CSPI dependent variable. The BI Rate variable partially has no significant effect and positively correlates to the CSPI dependent variable. Inflation variable partially has no significant effect and positively correlated to the CSPI dependent variable.